The use of biochar and charcoal as soil amendments to improve allelochemical-laden soils in the landscape - Ebeheakey, Asi Alberta (2014)
A thesis submitted to the school of research and graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the award of Master of philosophy (Mphil landscape Studies) degree,